A conceptual framework: examination the role of physical environment on Airbnb experiences/ Nor Maizana Mat Nawi ... [et al.] - Mat Nawi, Nor Maizana; Shahril, Zurena@Rena; Hamid, Rasidah; Nik Hashim, Nik Alif Amri (Faculty of Hotel & Tourism Management, Universiti Teknologi MARA, 2022)
Airbnb accommodation in Malaysia is increasingly competing with the hotel industry on the guest experience. However, the role of physical environment and perceived value is seen as a critical factor in maintaining growth for Airbnb's success. The physical environment and perceived value are essential elements to discover because research on this issue is underrepresented in the hospitality literature. The purpose of this article is to construct and test a model by proposing a new conceptual framework consisting of the physical environment with two dimensions, namely ambience and amenities, perceived value and guest satisfaction, to better understand a recent phenomenon in the accommodation sector. Also, the Airbnb accommodation will focus more on its usage of the two A's, namely ambience and amenities, to encourage guests to interpret their experiences through these aspects. This conceptual study will employed a structural equation model (SEM) to test the model proposed. Later, the findings will expand knowledge through hospitality services with an examination of variables that lead to guest satisfaction.